Fire Suppression Agents Combined with Gasoline in Aquatic Ecosystems: A Mixture Approach - Daniel, Gabriela [UNESP]; Silva, Ana Rita R.; Souza Abessa, Denis Moledo de [UNESP]; Loureiro, Susana (Wiley-Blackwell, 2020)
Fire suppression agents are recommended for extinguishing fires by flammable liquids and frequently end in water bodies, combined with the fuels. There is a lack of toxicity information on these commercial formulations and the effects of mixtures of fire suppression agents and fuels. The aim of the present study was to evaluate the toxic effects of different fire suppression agents, the gasoline water-soluble fraction (GWSF), and mixtures of each fire suppression agent and GWSF. Individual tests were performed with Daphnia similis and Artemia sp.; the most toxic fire suppression agents to D. similis and Artemia sp. were F-500 (R), Cold Fire (R), Agefoam (R), and Kidde Sintex (R) 1%; the GWSF was the least toxic. The concentration addition model was used to predict the mixture effects and evaluate synergism/antagonism, dose ratio dependence, and dose level dependence. Cold Fire with GWSF showed dose level deviation to D. similis, marked mainly by synergism; for Artemia sp., the dose ratio pattern was predicted, with a synergistic response mainly by Cold Fire. Agefoam and GWSF behaved additively for D. similis and dose ratio for Artemia sp., with synergism being caused by Agefoam. Kidde Sintex 1% with GWSF were dose ratio for both organisms, with Kidde Sintex 1% being responsible for synergism. Our results show that some mixtures of fire suppression agents and GWSF may cause toxicity to aquatic organisms, posing risk in a real environmental scenario, such as a major fire combat. Environ Toxicol Chem 2020;00:1-13. (c) 2020 SETAC
Keywords: Aqueous film– forming foam; Ecotoxicology; Aquatic toxicology; Environmental emergency; Mixtures; Fire suppression agents